2022
DOI: 10.3389/fncom.2022.1040646
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic control of eye-head gaze shifts by a spiking neural network model of the superior colliculus

Abstract: IntroductionTo reorient gaze (the eye’s direction in space) towards a target is an overdetermined problem, as infinitely many combinations of eye- and head movements can specify the same gaze-displacement vector. Yet, behavioral measurements show that the primate gaze-control system selects a specific contribution of eye- and head movements to the saccade, which depends on the initial eye-in-head orientation. Single-unit recordings in the primate superior colliculus (SC) during head-unrestrained gaze shifts ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 82 publications
1
5
0
Order By: Relevance
“…Figure 1b presents a possible scheme for eye-head gaze control by the SC population (after 65 ). Behavioral studies have shown that eyes and head are both driven by their own goals: an oculocentric gaze error for the eye vs. a craniocentric error for the head 14 , 66 , which requires feedback from an eye-in-head position signal (red arrows in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1b presents a possible scheme for eye-head gaze control by the SC population (after 65 ). Behavioral studies have shown that eyes and head are both driven by their own goals: an oculocentric gaze error for the eye vs. a craniocentric error for the head 14 , 66 , which requires feedback from an eye-in-head position signal (red arrows in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1B illustrates a possible extension of the model in Fig. 1A to eye-head gaze control by the SC population (after Alizadeh and Van Opstal, 2022b). Behavioral studies have shown that eyes and head are both driven by their own goals: an oculocentric gaze error for the eye, vs. a craniocentric error for the head (Goossens and Van Opstal, 1997;Freedman and Sparks, 2000).…”
Section: Sc: Gaze Shiftsmentioning
confidence: 99%
“…Recenty, we proposed a quantitative model for the SC and the downstream control circuits for the eyes and head that can account for these behaviors (Kasap and Van Opstal, 2018;Van Opstal and Kasap, 2019;Alizadeh and Van Opstal, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Recenty, we proposed a quantitative model for the SC and the downstream control circuits for the eyes and head that accounts for these behaviors (Kasap and Van Opstal, 2018;Van Opstal and Kasap, 2019;Alizadeh and Van Opstal, 2022b). The major novelty of our model with respect to earlier proposals (Laurutis and Robinson, 1986;Guitton and Volle, 1987;Guitton, 1992;Galiana and Guitton, 1992;Goossens and Van Opstal, 1997;Freedman, 2001;Kardamakis et al, 2010;Sağlam et al, 2011;Daye et al, 2014) resides in the assumed role of the midbrain Superior Colliculus (SC) in the control of gaze shifts.…”
Section: Introductionmentioning
confidence: 99%